PERDAGANGAN KARBON SEBAGAI INSTRUMEN ADVOKASI KEADILAN SOSIAL: TINJAUAN TERHADAP PERLINDUNGAN DAN PEMBERDAYAAN MASYARAKAT LOKAL DALAM KERANGKA PEMBANGUNAN BERKELANJUTAN - Alya Maya Khonsa Rahayu; Agatha Jumiati; Zepiko Ferera (Jurnal Ilmiah Advokasi, 2026)
Climate change has encouraged the development of various legal and economic instruments to reduce greenhouse gas emissions, one of which is carbon trading. Although carbon trading has evolved as a market-based mechanism within the international climate regime, limited legal scholarship has examined its economic value for local communities and its relationship with social justice and sustainable development. This study aims to analyze the legal and economic position of carbon trading, examine the conceptual distinction between carbon trading, carbon tax, and excise duties within the Indonesian legal system, and evaluate the implications of carbon trading for improving the welfare of local communities from the perspective of social justice. This research employs a normative legal method using statutory and conceptual approaches through the analysis of legislation, legal doctrines, and relevant scientific literature. The findings indicate that carbon trading functions as a market-based legal instrument that promotes greenhouse gas emission reductions through economic incentives while simultaneously creating economic opportunities for local communities through conservation financing, community-based forest management, and green economic development. The study further finds that carbon tax differs fundamentally from excise duties in both legal concept and regulatory objectives, and therefore the two instruments cannot be equated within the Indonesian taxation system. Accordingly, the successful implementation of carbon trading requires integrated policies that ensure legal certainty, protect the rights of local communities, promote equitable distribution of economic benefits, and support the achievement of sustainable development goals.Keywords: carbon trading; local communities; economic value; social justice; sustainable development